Ginger (Zingiber officinale) based intercropping systems for enhancing productivity and income – a farmers’ participatory approach - RYMBAI, H; DAS, ANUP; MOHAPATRA, K P; TALANG, H D; NONGBRI, B; LAW, I (The Indian Journal of Agricultural Sciences, 2021)
Ginger (Zingiber officinale Rosc.), an important medicinal and aromatic rhizomatous spice crop has potential for improving the livelihood of hill farmers. A participatory field study was conducted in 35 farmers' field of Mawthei village (25°44’18.57” N, 91°58’27.89” E and elevation of 1000-1200 m amsl) of Meghalaya to identify a sustainable ginger based intercropping system to improve income of the resource poor hill farmers. Results indicated that fresh rhizome weight was the highest in ginger as sole crop (208 g/plant) which was at par with ginger + soybean, ginger + maize + French bean and ginger + groundnut intercropping systems. Ginger + maize + French bean + pumpkin system recorded the highest Ginger Equivalent Yield (GEY, 9.24 t/ha), i.e. 15.20% higher than sole ginger crop yield. Maximum Land Equivalent Ratio (LER) was obtained in ginger + maize + French bean (2.63) followed by ginger + maize + French bean + pumpkin (2.57) system. The highest net returns were recorded with ginger + maize + French bean + pumpkin (₹ 3.36 lakh/ha) followed by ginger + maize + French bean (₹ 3.17 lakh/ha) systems. The intercropping of ginger + groundnut recorded highest benefit cost ratio (3.42), followed by ginger + pumpkin and ginger + maize + French bean. Thus, adoption of ginger + maize + French bean + pumpkin and ginger + maize + French bean intercropping systems may help in improving the economic conditions of the hill farmers in eastern Himalayas.